(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the manner of reflecting great values in poetic expression in the author’s consciousness and thinking. In particular, it is emphasized that the closeness of the relationship between the author and the universe lays the foundation for the integration of philosophical and aesthetic lighting. As a result, scientific and theoretical reflections are carried out on the fact that a person as a person finds his place in society, that the artistic reflection of moral norms is re-modified in the writer’s mind